Local politicians in the age of new media - Bjørnå, Hilde; Steinveg, Beate; Hernes, Hans-Kristian (Frontiers in Political Science, 2022)
This paper discusses the impact of new media on local politics and politicians in a highly digitalized and advanced democracy. Through case studies and interviews of elite representatives in three Norwegian municipalities, the paper’s ambition is to gain further understanding of the use of new media at the local political level and how new media influences and shapes the role as local political representatives. To this aim we use established literature on new media use in campaigns and as self-promotion, and literature on new media and democracy. Main findings are that the use of new media, particularly Facebook, is widespread, that new media has hardened the political debate and is especially straining for younger women. New media contributes to “professionalizing” political communication as it requires more strategic thinking around messaging and engagement. New media has in some ways contributed to bringing local representatives closer to the citizens and provide valuable information, but also produce “echo-chamber” effects. In sum, new media provides challenges and opportunities that may impact the willingness to stand as representatives and contribute to creating new ‘types’ of local politicians.